The Gold Mine: A Post-singularity Utopia - Clear, Nic (Architecture Image Studies, 2020)
The Gold Mine is an architectural project for a post-scarcity, post-singularity city set on Canvey Island. The project is intended to test the application of speculative ideas taken from literary science fiction combined with concepts currently being developed in the Nano-Bio-Info-Cogno technologies and framed within the context of a formal architectural project. The Gold Mine is seen as a speculative architectural design intended to ask ‘what-if’ questions about the nature of our cities and re-ignite debates around the concept of Utopia, proposing a radically different model of the human organisation at a time when neo-liberal ideologies dominate our thinking on the city.